Consumer knowledge, attitude and concern in consuming contaminated peanut-based products - Hassan, Nur Adibah (2018)
In Malaysia, peanut has been consumed in form of snacks, or better known as peanut-based products (roasted peanut, peanut candy, confectioneries, pastry) and as main ingredients in several local dishes, most notably the satay sauce. However, peanut-based products have been associated to contamination such as Aflatoxin (AF), Salmonella and possible metal pieces. Food products contamination is a serious issue and it is most related to food safety issues. Issues of contaminated peanut-based products have been mentioned from various parties to minimize the risks of peanut-based products contamination. The general objective was to determine the consumer knowledge, attitude and concern in consuming contaminated peanut-based products. Meanwhile, the specific objectives were to determine consumer’s knowledge, attitude, and concern level in consuming contaminated peanut-based products, to determine the significant association between consumer socio-demographic profiles and consumer’s knowledge, attitude and concern level in consuming contaminated peanut-based products, to examine the relationship between knowledge, attitude and concern level in consuming contaminated peanut-based products and to investigate the most influential factors that influence consumers’ behaviour in consuming contaminated peanut-based products. Purposive sampling was used as sampling method with 1,263 consumer was selected as respondents to represent Klang Valley. A structured questionnaire was used in order to gather the data. Four analyses were used to achieve the objectives of the study, namely descriptive analysis, Chi-square analysis, Pearson correlation analysis and logistic regression analysis. The result showed that about 86.3% of the consumers have inadequate knowledge level towards consuming contaminated peanut-based products. In terms of attitude level, about 74.8% of the consumers have unfavourable attitude towards consuming contaminated peanut-based products due to the lack of knowledge towards issues discussed. However, 81.6% of the consumers have high concern towards consuming contaminated peanut-based products. Pearson correlation analysis was conducted to examine the strength of relationship between knowledge, attitude, and concern level in consuming contaminated peanut-based products. The results showed the strength association correlation between knowledge, attitude, and concern level is moderate to low with positive relationships and significant at 1% level of significance. Chi-square analysis was carried out to determine the association between consumers’ socio-demographic profiles and knowledge, attitude, and concern level. Age, gender, religion, education level, and income were significantly associated with consumers’ knowledge level towards consuming contaminated peanut-based products. Age, religion, and marital status were significantly associated with consumers’ attitude level towards consuming contaminated peanut-based products, while religion, income, and marital status were significantly associated with consumers’ concern level towards consuming contaminated peanut-based products. Logistic regression analysis was conducted to investigate the most influential factors that influence consumers’ behaviour in consuming contaminated peanut-based products. The study found that socio-demographic profiles such as religion and household number had significant relationship with frequency of consumers experience behaviour in consuming contaminated peanut-based products. The variables of knowledge, attitude, and concern also had significant relationship with frequency of consumers experience in consuming contaminated peanut-based products. As an improvement guideline for upstream industry to control the contamination peanut-based products, government should focus on downstream, particularly the consumers by educating public knowledge on contamination symptoms of peanut-based products. Frequent press release, campaign and intervention through mass and social media could increase the public knowledge on the danger of peanut-based products contamination, as well as reducing the risk of consuming contaminated products among consumers.